PEMANFAATAN PASCA PANEN DAN UPAYA PENINGKATAN NILAI EKONOMI SAYUR SAWI SENDOK DALAM PEMBUATAN ES KRIM DI KELURAHAN BALUWARTI - Mawarno, Binardo Adi Seno; Rokhmah, Laela Nur; Milatina, Nada Ila; Dewi, Yenita Cahya (LPPM Universitas Nusa Mandiri, 2026)
The main achievement indicator of this community service program is the creation of a functional ice cream product from locally grown mustard greens. This local vegetable was chosen because it is readily available as a result of cultivation by residents at the “Healthy Food Corner” in the Baluwarti neighborhood, a special area dedicated to food crop cultivation. The community service was carried out at the Keraton Kasunanan hall, Baluwarti Village, Pasar Kliwon District, Surakarta City, through lectures and discussions on the potential of the main raw material (mustard greens), ice cream making practices, and sensory evaluation of the product. The activity received positive responses from 30 participants with the creation of new products that were not yet available on the market and were liked by the participants based on acceptance level tests. The post-test results also showed an increase in participants' knowledge and skills regarding raw materials and food product innovation, which was 59.28%. Participants were actively involved from raw material preparation, processing, to sensory evaluation of ice cream. Over 90% of participants expressed satisfaction, and the activity had a positive impact on the utilization of local vegetables. The product innovations resulting from this initiative represent a concrete step toward utilizing local resources, increasing the economic value of mustard greens, and creating opportunities for the UMKM and the creative economy among the community.